1997
DOI: 10.1002/(sici)1097-0274(199706)31:6<733::aid-ajim10>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Coronary heart disease risk factors in employees of Iowa's Department of Public Safety compared to a cohort of the general population

Abstract: The prevalence of coronary heart disease (CHD) risk factors in law enforcement personnel compared to that in the general population was studied by determining the predicted 10‐year risk for developing CHD (CHD10, expressed as %) in subjects from the Iowa Department of Public Safety and comparing it to the average CHD10 for similarly aged subjects in the Framingham Heart Study cohort. The Iowa data included measures on 388 men from 30 to 64 years old, 246 of whom were measured in 1980–1981 and again in 1992–199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In summary, volunteer CFA firefighters' 10-year CHD risk was greater than other volunteer firefighter 8 and paid emergency service 14,16,39,40 populations. In comparison, CFA firefighters were older and had higher BP than other emergency services, 8,14,16,39,40 which, therefore, could contribute to their higher overall CHD risk.…”
Section: Commentmentioning
confidence: 80%
See 2 more Smart Citations
“…In summary, volunteer CFA firefighters' 10-year CHD risk was greater than other volunteer firefighter 8 and paid emergency service 14,16,39,40 populations. In comparison, CFA firefighters were older and had higher BP than other emergency services, 8,14,16,39,40 which, therefore, could contribute to their higher overall CHD risk.…”
Section: Commentmentioning
confidence: 80%
“…49 Therefore, given the various fire ground stressors, firefighting work could act like a secondary risk factor for adverse CHD events among susceptible personnel. Volunteer CFA firefighters' 10-year CHD risk appears high when compared with other volunteer 8 and paid emergency service 14,16,39,40 populations. Unlike their paid counterparts, volunteer firefighting departments do not typically require their firefighters to meet stringent health employment standards nor do they require them to exercise or train regularly.…”
Section: Commentmentioning
confidence: 86%
See 1 more Smart Citation
“…1,2 It has been reported by researchers that due to enormous stress, police officers suffer from different physiological disorders, such as gastrointestinal, insomnia, psychological disorders,family dysfunction 1,[3][4][5][6][7][8][9] and cardiovascular disorders 10,11 than the general population. The objective of the study was to estimate the burden of individual and aggregated CVD risk factors and predict the 10 year risk of fatal and non-fatal cardiovascular event in this population using Framingham risk score.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of police officers have also shown a higher prevalence of BMIs above 25 (level above normal weight) among officers (82.6%) than among the general population (74.7%), which could be misleading with regard to the potential risk for metabolic and cardiovascular diseases [33,34]. Additionally, Hartley et al [35] have verified the association between depression symptoms and metabolic syndrome in 450 policemen (410 Buffalo, New York Police Officers and 130 Spokane Heart Study Police Officers).…”
mentioning
confidence: 98%